2017
DOI: 10.1002/mc.22665
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mitochondrial apoptotic pathway in triple negative breast carcinoma cells by methylglyoxal via generation of reactive oxygen species

Abstract: Triple negative breast cancer (TNBC) tends to form aggressive tumors associated with high mortality and morbidity which urge the need for development of new therapeutic strategies. Recently, the normal metabolite Methylglyoxal (MG) has been documented for its anti-proliferative activity against human breast cancer. However, the mode of action of MG against TNBC remains open to question. In our study, we investigated the anticancer activity of MG in MDA MB 231 and 4T1 TNBC cell lines and elucidated the underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…MG is a crucial factor in the induction of oxidative stress and in the generation of reactive oxygen species (ROS) [ 40 , 44 , 45 , 46 , 47 , 48 ]. The major route by which MG generates ROS is by directly modifying proteins, e.g., mitochondrial membrane proteins [ 49 , 50 ], antioxidant enzymes [ 50 , 51 ], endothelial nitric oxide synthase [ 52 ] and NADPH oxidase [ 53 ]. Moreover, MG, mainly through MG-H1, which serves as a ligand for the receptor of AGEs (RAGE), is an important pro-inflammatory agent [ 40 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…MG is a crucial factor in the induction of oxidative stress and in the generation of reactive oxygen species (ROS) [ 40 , 44 , 45 , 46 , 47 , 48 ]. The major route by which MG generates ROS is by directly modifying proteins, e.g., mitochondrial membrane proteins [ 49 , 50 ], antioxidant enzymes [ 50 , 51 ], endothelial nitric oxide synthase [ 52 ] and NADPH oxidase [ 53 ]. Moreover, MG, mainly through MG-H1, which serves as a ligand for the receptor of AGEs (RAGE), is an important pro-inflammatory agent [ 40 , 54 , 55 , 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…53 As a result, MGO concentrations tested by MG-SLNP in whole blood were slightly higher, which might be of great biological significance. Owing to abnormally high levels of MGO-induced oxidative stress, 54 bright green fluorescence derived from 2,7-dichlorodihydrofluorescein diacetate (DCFH-DA) was observed in mouse kidney slices of the db/db group (Figure 4H). Significant histological morphological changes in the kidney in Figure 4I show that the mesangial region widened and the mesangial matrix increased, which was mainly caused by hyperinsulinemia, verifying the establishment of T2D.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…As expected, the results showed a concentration-dependent increase in levels of Cyt c. This could result in the formation of apoptosome complex which can further activate caspase-3. 49 Moreover, in a majority of cancers and especially in TNBC, the level of antiapoptotic protein Bcl-2 is usually high, leading to inhibition of the permeability of mitochondria and is pivotal for the activation of apoptosis via mitochondria. 50−52 In our current research, we have demonstrated significant loss of MMP and hence as the next step, we also determined the level of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%